Traditional Reindeer Herding in Russia: Legal Issues of Land Provision and Rational Use - V. Kryazhkov (Publishing House V.Ема, 2025)
Legal regulation governing indigenous rights related to the Northern lands and traditional economic activities began to take shape in the late Soviet and post-Soviet periods, when legislators established a special legal regime of land use for indigenous peoples, including for reindeer herding. Later, federal legislation was formulated based on international legal norms and the provisions of the Constitution of the Russian Federation, which guaranteed the rights of indigenous peoples to use the land as a material basis for their traditional activities. This article demonstrates that the current Russian legislation in this regard is merely symbolical, fragmentary, contradictory, and has gaps. The legislation of the Russian regions, in which reindeer herding is developing, partly compensates for the above-mentioned shortcomings. The most complete implementation is seen in Yakutia and the Nenets Autonomous Okrug regions, where land plots are assigned to reindeer owners with the obligation to use the allocated lands in accordance with land management projects and regulations that protect against the depletion of natural resources. This article references both domestic and foreign experience in this area and offers legislative proposals from an ethnocultural perspective that justify the right of northern indigenous peoples to reindeer herding as an integral form of their traditional economic practices. In this context, the free use of lands for reindeer herding should be guaranteed in the regions of traditional dwelling and economic activity; additionally, special regulations should be implemented to ensure the environmentally sustainable use of those lands alongside some adaptation measures that can be taken to protect reindeer herders from climate change. The abovementioned provisions can be incorporated in land and environmental legislation, as well as in the federal law on reindeer herding.